The study of syngas through the partial oxidation of methane and its role as an energy source - Stoops, Parker (Kansas State University, 2022)
The goal of this thesis is to explore the methods for syngas production with a focus on the Partial Oxidation of methane (POX) and to study its role as a source of energy. In our experimentation we studied the potential of a batch detonation method in a constant volume chamber. From these experiments, we found that the detonation products followed our predictions based on the POX reaction. Following this we moved to test the possibility of repurposing a spark ignition internal combustion engine for a continuous flow of syngas. Through these experiments we found that FT-IR and GC shows that syngas is producible.
Keywords: Synthesis gas; Hydrogen production; Spark ignition (SI); Engine